THE INFLUENCE OF ELECTRONIC WORD OF MOUTH (EWOM) AND BRAND IMAGE ON CUSTOMER PURCHASE INTENTIONS AT TRAVELOKA ONLINE TRAVEL AGENCY - Ruata, Dylan Y.; Mangantar, Marjam M.; Pandowo, Merinda H. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
This study was made to identify the influence of Electronic word of mouth, and Brand image on customer Purchase intention. Most people would do some or even extensive research of their product or services before purchasing stuffs. Reviews and experience stated by previous customer surely affects the purchase intention of other customers, especially people in this technology advanced era. Customer would easily find their needs on the internet and tends to articulate themselves even more on the internet. This is related with the Brand image factor that may influence customer purchase intention. People would simply see the popularity of the brand and tends to try or even repeatedly use it. Hence, it is important for companies especially online travel agencies that they maintain or even improve their good image and increase their presence on the internet. The types of method used in this research is quantitative method with a sample population of 100 acquired from respondents who had previously used Traveloka online travel agency using purposive sampling method. While the tests and data analysis are done using the SPSS 26 software. Result found in this research shows that both Electronic word of mouth (X1) and Brand image (X2) has significant influence on customer Purchase intention (Y). People tend to consider buying a product or services from a bigger company with more fame. And reviews that appears on the internet will affect customers purchasing intentionÂ Keywords: Brand image, purchase intention, eWOM